(untitled) (AYUSHDHARA, 2021)
Pre menstrual syndrome (PMS) is distressing psychological, physical and/ or behavioural symptoms. It occurs during the luteal phase of menstrual cycle. The significant regression of symptoms comes with onset of or during the period. PMS can also be defined as a combination of emotional, physical and psychological disturbances. It occurs after a woman’s ovulation, which gets end with onset of her menstrual flow. Here, in this review a detailed explanation about its etiology, symptoms, signs, diagnosis, differential diagnosis and its treatment are being described. Ayurveda points of view regarding PMS are also being described. Premenstrual syndrome can be probably correlated with Rituvyatita Kalaja Pitta Vata Vriddhi. As Vata dosha plays important role in aggravating the other Doshas as well. Vata Dosha imbalance causes the imbalance state of other Doshas causing premenstrual syndrome. Vata in association with Pitta and Kapha simultaneously vitiates Manodosha and Rasadhatu. Mithyahar vihar is the Samanya nidana for this syndrome.